The type specimen and generic placement of Tridactylus galla Saussure, 1895 (Orthoptera: Caelifera: Tridactylidae) - Heads, Sam W.; Hollier, John (Zootaxa, 2016)
Tridactylus galla was described by Henri de Saussure (1895) on the basis of a single adult female collected during Vittorio Bottego’s first expedition to the Horn of Africa in 1892 and 1893. The species appears in lists compiled by Fenizia (1896), Lucas (1898) and Kirby (1906), but aside from a brief mention by Günther (1995), is entirely overlooked by subsequent authors and is absent from Otte’s (1997) catalogue. During the course of compiling an annotated catalogue of the Orthoptera described by Saussure (Hollier and Heads, 2012) we were able to relocate the type of Tridactylus galla in the collection of the Museo Civico di Storia Naturale “Giacomo Doria” in Genova, Italy. Our examination of the specimen confirmed Günther’s (1995) assertion that its placement in Tridactylus Olivier, 1789 is erroneous, and the species is herein formally transferred to the genus Xya Latreille, 1809.